Password-based Selective Linkable Convertible Ring Blind Signature. Issue 2 (August 2019) - Zhang, Yulei; Song, Tingting; Zhang, Yongjie
Abstract: Ring signature has become an important way of privacy protection because of its anonymity and the spontaneity of ring members. It has been widely used in the field of information security. Password-based alternative linkable convertible ring blind signature scheme combines the advantages of strong anonymity of ring signature and blindness of blind signature to signature message, and adds the optional linkable and convertible characteristics, which makes it more secure than other schemes, and can also transform ring signature into ordinary signature in special occasions. At the same time, under the random oracle model, the scheme satisfies the unforgeability under the adaptive selection message attack. Performance analysis shows that the scheme has high operating efficiency.